Comparison of fluid‐fluid interfacial areas measured with X‐ray microtomography and interfacial partitioning tracer tests for the same samples. Issue 7 (16th July 2016) - McDonald, Kieran; Carroll, Kenneth C.; Brusseau, Mark L.
Abstract: Two different methods are currently used for measuring interfacial areas between immiscible fluids within 3‐D porous media, high‐resolution microtomographic imaging and interfacial partitioning tracer tests (IPTT). Both methods were used in this study to measure nonwetting/wetting interfacial areas for a natural sand. The microtomographic imaging was conducted on the same packed columns that were used for the IPTTs. This is in contrast to prior studies comparing the two methods, for which in all cases different samples were used for the two methods. In addition, the columns were imaged before and after the IPTTs to evaluate the potential impacts of the tracer solution on fluid configuration and attendant interfacial area. The interfacial areas measured using IPTT are ∼5 times larger than the microtomographic‐measured values, which is consistent with previous work. Analysis of the image data revealed no significant impact of the tracer solution on NAPL configuration or interfacial area. Other potential sources of error were evaluated, and all were demonstrated to be insignificant. The disparity in measured interfacial areas between the two methods is attributed to the limitation of the microtomography method to characterize interfacial area associated with microscopic surface roughness due to resolution constraints. Key Points: Comparison of the two methods available for measuring interfacial area Different magnitudes of interfacial area were obtained The disparity is attributed to resolution constraints for the XMT method